Family mediation: problems of negotiability and domestic violence in the focus of professional discourse (on the materials of sociological research) - O. E. Gracheva; I. V. Mkrtumova (Цифровая социология)
The article is devoted to a sociological analysis of the opinions of family mediation specialists on the problems of spousal negotiability and domestic violence. The analysis is based on the results of two sociological surveys of representatives of the expert community who have participated in family mediation events (N = 416). The questionnaires have been filled in by participants of the round tables “Mediation and personal negotiability in a family conflict” (June 19, 2024) and “Mediation and family violence: balance of interests” (28 February, 2024), organised by the Centre for Mediation and Social and Legal Assistance of the Moscow “Sodeystvie” Centre. The authors have determined the relevant strategic vectors and practices of the social construction of a mediation solution for family disputes of spouses with children during the divorce. The study is based on the concepts of R. Fisher and W. Uri describing theoretical and applied aspects of mediation (the Harvard project) as well as on the provisions of the theory of social construction of reality by P.L. Berger and Th. Luckmann. The main methods of empirical research are questionnaire surveys of family mediation specialists, specialists of family centres, psychologists, teachers, psychiatrists, bailiffs, lawyers on this topic as well as methods of observation and analysis of the divorcing spouses’ behaviour who came to the first information meeting before mediation conducted by the authors of the article. As a result, specific features of family problems leading to the breakdown of family ties have been identified, including problems of family violence, parental alienation, and negotiability of spouses. In conclusion, important expert opinions have been obtained; in particular, the authors have established the need to develop an additional section in the opinion of the guardianship and custody agency aimed at identifying the signs of family violence and parental alienation (the document is sent to the court before the divorce of spouses with children). A new management approach for mediation resolution of family conflicts of spouses with children has been developed. Its purpose is to improve the systematic interdisciplinary work of specialists of mediation centres.